PROPHETIC EDUCATION PORTRAIT OF POPULAR LITERATURE IN INDONESIA - Hardiyanto, Fahrudin Eko; Prabaningrum, Dyah (CENTRAL ASIA AND THE CAUCASUS, 2022)
Character education experts have agreed that there is a need for role models for students. However, in the digital era and human alienation from one another, it is difficult for people to find the expected role models. Therefore, we need a figure who is right and close to the community as an example. This figure is expected to be an example that will remain in their minds. One of the most possible strategic steps to present this figure is by presenting it in literary works. Such a figure is called an imaginary figure. The literary work media is novel. Through novels, characters are designed in such a way as to be able to provide character education to community. In this regard, the didactic character for community is prophetic character education. As for literary works which publicity is wide and easily accepted are popular literary works. In this article the popular literary works that are analyzed are Keluarga Cemara dan Sawitri dan Tujuh Pohon Kelahiran (Cemara Family and Sawitri and the Seven Trees of Birth). The analytical method used in this study is the hermeutic method. The result of the research in three popular novels is that there are characters who become portraits in carrying out prophetic ethics as character education in everyday life.